Salivary biomarkers and burning mouth syndrome: a systematic review and meta-analysis of the literature - Kappes Florian; Kerrad Samy; Grémeau-Richard Christelle; Devoize Laurent (EDP Sciences, 2023)
Introduction: Burning Mouth Syndrome (BMS) is defined by a burning sensation or intraoral dysesthesia without obvious causal lesion. Despite the development of research, diagnostic aids for this syndrome are non-existent and treatments are partially ineffective. Some studies have shown changes in salivary composition, viscosity or flow in patients with BMS. The evaluation of the salivary biochemical characteristics of patients with BMS could then help to better understand the pathogenesis of this disease. The objective of this meta-analysis is to perform a qualitative and quantitative synthesis of the literature concerning the salivary biomarkers present in patients with BMS in comparison to healthy subjects. Materials and methods: The PubMed, Web of Science and Cochrane databases were searched to identify articles corresponding to the defined inclusion criteria. Review Manager 5.4.1 software was used to perform the quantitative analysis. Results: The quantitative analysis included 15 articles and found a significant increase in salivary concentrations of cortisol and immunoglobulin A (IgA) with a standardized mean difference SMD = 0.53 and a 95% confidence interval CI [0.33 to 0.74] and SMD = 0.32 to 95% CI [0.10 to 0.55] respectively. For calcium and copper, the analysis found no significant difference in patients with BMS with SMD = 0.06 at 95% CI [-0.19 to 0.32] and SMD = -0.19 at 95% CI [-0.44 to 0.06]. Finally, for magnesium, the analysis found a probable decrease with SMD = -0.29 at 95% CI [-0.52 to -0.06]. Four other biomarkers (potassium, alpha amylase, zinc and total protein) showed too high levels of heterogeneity (I² > 44%) to be able to interpret the results with confidence. Discussion: This strong heterogeneity can be explained by different saliva sampling methods or biomarker measurement techniques that are not strictly identical between the studies. In addition, some saliva samples may have undergone blood contamination which may bias the results. Conclusion: This meta-analysis nevertheless confirms all the interest of focusing on salivary biomarkers in BMS patients; the measurement of cortisol and/or salivary IgA could be a line of research for the establishment of a standardized biological assessment. Nevertheless, the number of available studies being low and of variable methodological quality with a limited number of patients, additional studies are necessary to give a firm and definitive conclusion.